IKLAN LAYANAN MASYARAKAT TENTANG BAHAYA NARKOBA BAGI GENERASI MUDA: PUBLIC SERVICE ADVERTISEMENT ABOUT THE DANGERS OF DRUGS FOR THE YOUNG GENERATION - Meirina Lani Anggapuspa; Hendro Aryanto; Muh. Ariffudin Islam; Aryanto, Hendro (Jurnal Dimensi Seni Rupa dan Desain, 2025)
Gayungan Village has a variety of facilities and community services, such as village offices, places of worship, health centers, schools, and other public facilities. Some of the flagship programs owned by Gayungan village are community development and empowerment, including economic factors, socio-cultural factors, the environment and others. On the other hand, there is a serious problem that can threaten the young generation in Gayungan village, namely drugs. There is no media as a reminder as well as prevention about the dangers of drugs around Gayungan village. With the emergence of these problems, it is hoped that the younger generation in Gayungan sub distric will stay away from these prohibited items. The data collected through field observations and interviews. This study it uses 5W1H data analysis techniques in accordance with the needs of the problems being researched to determine effective and communicative Community Service Advertisements.